Efektivitas Media Komik Terhadap Perubahan Perilaku Pemilihan Jajanan Sehat pada Siswa Sekolah Dasar - Yessi Alza; Lidya Novita; Zahtamal Zahtamal (Jurnal Kesehatan Komunitas, 2023)
In elementary school-age students (SD), most of their food comes from the consumption of snacks in the school canteen. Currently time, there is a great need for learning media that contains information about healthy school snacks. Media in the form of comic storybooks is a medium that is very liked by children.  The aim of this study is to know the effectiveness of comics media on behavioral changes in choosing healthy snacks in elementary school students. This study is a quasi-experimental study with a non-equivalent control group design. Hypothesis analysis using paired sample t-test and independent sample t-test. The number of samples in this study was 55 students who were taken by purposive sampling with several inclusion criteria at two SD in Pekanbaru City. Wilcoxon's test of knowledge and attitudes showed p value <0.05 in the intervention group and the control group. This shows that the use of educational comics for healthy snacks for elementary school students has proven to be significant in increasing students' knowledge and behavior in choosing healthy snacks. However, the comic was not yet effective in increasing knowledge and behavior as seen from the mean value in the control group which was greater than the intervention group in all research variables.